LITERATURE REVIEW: THE INFLUENCE OF PERFORMANCE APPRAISAL ON EMPLOYEE PERFORMANCE WITH THE ROLE OF WORK ENVIRONMENT MEDIATION AND MANAGEMENT STYLE - Yuni Nur Wulandari; Agung Surya Dwianto (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the Influence of performance appraisal on employee performance by considering the mediating role of the work environment and management style. Performance appraisal is a strategic tool in human resource management to assess employee achievements and provide feedback. However, its effectiveness is often influenced by the conditions of the work environment and the leadership style applied by the organization. Through a literature review of Scopus-indexed journals from 2020–2025, this study identifies the relationship between performance appraisal, work environment, management style, and employee performance. The review results show that a fair and transparent appraisal system can enhance employee motivation and performance. The work environment acts as an important mediator because comfortable and supportive conditions influence employees' responses to feedback. In addition, transformational and participative management styles strengthen the positive impact of appraisal